Kajian Atas Kasus-Kasus Pelanggaran Ham TKW di Luar Negeri (Studi Kasus di Provinsi Sumatera Utara dan Disadur dari Hasil Penelitian Pusat Penelitian Hak-Hak Kelompok Khusus Tahun 2010) - Okky Chahyo Nugroho (Jurnal HAM, 2012)
Human Rights Violations of Labor Women that have emerged so far such as unpaid salary and abused by employers are crucial issues as it involves inter-state relations. On the one hand, Indonesia intends to preserve the harmony of Indonesia's diplomatic relations, but on the other hand such problems have brought grief issues for migrant workers and their families. The problem is that how the protection of migrant workers' rights who are working abroad is to be implemented; What are the causing factors of the occurence of human rights violations over maids working abroad, especially in Malaysia, and what steps needed to be taken to provide protection of migrant workers who are working abroad. The purpose of this study was to determine and to describe the practice of human rights protection. The method used is a qualitative approach with descriptive type (empirical juridic) and in answering the research problem, the research uses documentary research and field research. While the research is to evaluate the practice of human rights protection in order to find the causative factors of human rights abuses over migrant workers working in foreign countries, and measures that are needed to be done to prevent the occurrence of violations of Labor Women in the future.